Analysis of Carbon Peaking in Power Sector and its Impact on Promoting Whole-Society Carbon Emissions Reduction - Yuanbing ZHOU; Shining ZHANG; Fangxin HOU; Hongtao REN; Pengfei XU (Zhongguo dianli)
The carbon emissions from the power sector account for over 40% of the total carbon emissions in the energy sector, making it the primary battleground for emissions reduction in the energy sector. Against the backdrop of the whole society striving to achieve carbon peaking by 2030, the timing of power sector's carbon peaking is crucial for the end-use sectors and whole-society to achieve carbon peaking. Firstly, an analysis was conducted on the temporal relationship between the power sector's carbon peaking and the carbon peaking of the whole society and other sectors in countries that have already achieved carbon peaking. Secondly, theoretical derivations were made regarding the conditions that the power sector's carbon peaking needs to meet and the proportional requirements of non-fossil fuel power generation under different scenarios. Finally, a quantitative analysis was carried out on the impact of electricity substitution on emissions reduction in the end-use sectors and the whole society. The study indicates that the decline rate of carbon intensity in power production is a crucial constraint determining the power sector's carbon peaking. Under the baseline scenario that power generation reaches 13 TW•h in 2030, the proportion of non-fossil fuel power generation needs to reach 56.3%, which implies that the annual increase in newly installed capacity of wind and solar power should exceed 240 GW from 2023 to 2030 so that the power sector can achieve carbon peaking before 2030. The promotion of electricity substitution for emissions reduction in the whole society is influenced by the proportion of non-fossil fuel power generation in the total power generation. Only when the proportion exceeds a certain critical value can the synchronous emissions reduction in the end-use sectors and the whole society be achieved.